Authoritarian Rule and the Weaponisation of Natural Disasters: The Case of Myanmar from Cyclone Nargis to the COVID-19 Pandemic (2008–2021). (August 2022) - Passeri, Andrea
Myanmar's 2021 military coup paved the way for a ruthless weaponisation of the COVID-19 pandemic, aimed at crushing opposition groups and ethnic minorities who opposed the army's power grab. The manipulation of natural disasters for political purposes, however, is nothing new for Burmese praetorian regimes, which employed a similar strategy in the aftermath of the 2008 Cyclone Nargis in order to further marginalise and subjugate their internal enemies. To a large extent, such a callous decision stems from the powerful political implications brought about by natural disasters, which are perceived by authoritarian leaders as exogenous shocks capable of triggering a process of heightened popular contestation and regime change. In the case of Myanmar, this specific fear thus persuaded military rulers to weaponise the impact of natural calamities and health crises as part of a longstanding counterinsurgency playbook, centred on the so-called 'four cuts' doctrine. As a result, those who do not conform with the Bamar-Buddhist image of Myanmar professed by the army—or dare to criticise its dominant position in Burmese politics—have been deliberately excluded from post-disaster relief efforts, in what appears as a further testament of the junta's unwavering resolve in retaining the reins of power. Building upon the existing literature on the political implications of natural hazards in authoritarian settings, the following article sheds light on the drivers and rationale that persuaded Myanmar's Generals to weaponise humanitarian crisis against ethnic minorities and opposition forces, by looking at the two case-studies provided by Cyclone Nargis and the COVID-19 pandemic.